Cluster analysis identifies quantitative CT imaging-based subgroups in COPD subjects with pulmonary artery enlargement - Johnson, Shelsey W.; Ross, James C.; Nardelli, Pietro; Choi, Bina; Vanderpool, Rebecca R.; Pistenmaa, Carrie; Wells, J. Michael; San Jose Estépar, Raul; Washko, George; Rahaghi, Farbod N. (The European respiratory journal, 2025)
Pulmonary hypertension (PH) affects up to 60% of patients with COPD [1, 2]. When present, COPD-PH is a high-risk finding with associated mortality of up to 40% at 5 years [1, 3]. This mortality risk is multifactorial and in part reflects significant disease heterogeneity, which has limited the ability to identify effective treatments [4, 5]. Disease heterogeneity in COPD-PH has limited the ability to identify effective treatments. Chest CT is a non-invasive tool to advance disease sub-phenotyping. In COPDGene, cluster analysis identifies CT-based subgroups with differential mortality risk. https://bit.ly/4jEy5RT